Analysis of biomass and waste gasification lean syngases combustion for power generation using spark ignition engines. (January 2016) - Marculescu, Cosmin; Cenuşă, Victor; Alexe, Florin
Highlights: Gasification process applied to meat industry waste. Syngas properties analysis compared to MSW biogas and methane. Syngas and biogas comparing for use in Otto reciprocating engines. Otto reciprocating engine process modelling. Limits on using syngas in reciprocating Otto engines. Abstract: The paper presents a study for food processing industry waste to energy conversion using gasification and internal combustion engine for power generation. The biomass we used consisted in bones and meat residues sampled directly from the industrial line, characterised by high water content, about 42% in mass, and potential health risks. Using the feedstock properties, experimentally determined, two air-gasification process configurations were assessed and numerically modelled to quantify the effects on produced syngas properties. The study also focused on drying stage integration within the conversion chain: either external or integrated into the gasifier. To comply with environmental regulations on feedstock to syngas conversion both solutions were developed in a closed system using a modified down-draft gasifier that integrates the pyrolysis, gasification and partial oxidation stages. Good quality syngas with up to 19.1% – CO; 17% – H2 ; and 1.6% – CH4 can be produced. The syngas lower heating value may vary from 4.0 MJ/N m 3 to 6.7 MJ/N m 3 depending on process configuration. The influence of syngas fuel properties on spark ignition engines performances was studied in comparison to the natural gas (methane) and digestion biogas. In order to keep H2 molar quota below the detonation value of ⩽4% for the engines using syngas, characterised by higher hydrogen fraction, the air excess ratio in the combustion process must be increased to [2.2–2.8]. The results in this paper represent valuable data required by the design of waste to energy conversion chains with intermediate gas fuel production. The data is suitable for Otto engines characterised by power output below 1 MW, designed for natural gas consumption and fuelled with low calorific value gas fuels.